Search group algorithm for optimal allocation of battery energy storage with renewable sources in an unbalanced distribution system. Issue 1 (31st December 2023) - Mohanty, Sudipta; Nayak, Manas Ranjan; Behura, Diptimayee
ABSTRACT: In recent decades, numerous distributed energy resources (DER) have been linked to distribution networks. Among these wind turbine generators (WTG) are popular for their uncertain power fluctuations. Using battery-based energy storage devices (BESS) as a solution to these unwanted fluctuations might be a realistic option. However, the integration of BESS with WTG on a wider scale requires additional attention to the size, position, and charge-discharge schedules. This article discusses these perspectives in addition to the location and power penetration levels of WTGs. In addition, a new charge-discharge control model is created for deciding when batteries should be charged or discharged at each hour. A multi-objective optimization problem is created with the goal of optimizing the economic, environmental, and technological goals of the unbalanced distribution network (UDN). The optimization task is solved using a Search Group Algorithm (SGA). The planning model leverages the average demand of the feeder at a particular hour of the day as the decision criteria for charging or discharging the battery. The charging of the BESS devices is totally done by the WTG power output. Furthermore, the conservative and free-running discharge approaches of the battery are studied. The proposed approach is tested using IEEE 37 bus UDN and the results demonstrate improvement in distribution system performance by coordinating BESS dispatches appropriately. The active and reactive power loss reduction for the three-phase system were 30.4% and 30.8% for the free-run mode, respectively, while the same for the conservative mode was 40.3% and 37.4%.